2020
DOI: 10.29333/iji.2020.1325a
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Metacognition Based on Behavioural Learning to Improve Metacognition Awareness and Mathematics Ability of Students

Abstract: This study aims to develop student metacognition strategies based on behavioural learning in improving the mathematical abilities of students of mathematics education. There are two components developed in this study, namely: (1) Development of strategies to foster student metacognition based on behavioural learning, and (2) Development of learning tools consisting of: (a) test and search interview guidance levels or levels of student metacognition, and ( b) test students' mathematical abilities. The stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Thus, calculus learning emphasizes metacognition strategies in the learning process, so as to improve students' understanding of integral concepts. This is in line with the results of research by Salam et al [16], that through behavior-based metacognition strategies, it can improve the results of metacognition awareness and understanding of hereditary concepts for mathematics education students.…”
Section: Introductionsupporting
confidence: 90%
“…Thus, calculus learning emphasizes metacognition strategies in the learning process, so as to improve students' understanding of integral concepts. This is in line with the results of research by Salam et al [16], that through behavior-based metacognition strategies, it can improve the results of metacognition awareness and understanding of hereditary concepts for mathematics education students.…”
Section: Introductionsupporting
confidence: 90%
“…The aim of the study was to examine students" metacognitive skills in the problem-solving process, the differences between students who used metacognitive skills and those who did not, and their effects on the success of problem-solving. Various studies have shown that individuals with a high level of metacognitive awareness are much better at understanding what they read and consequently using what they understand in problem-solving (Aydem r & Kubanc, 2014;Balci, 2007;Dogan, 2013;Gelen, 2003;Gumus, 1997;Hassan, 2003;Johnson, 2002;Kiremitci, 2011;Mayer, 1998;Ozbilgin, 1993;Ozturk et al, 2020;Salam et al, 2020;Tohir, 2019;Vadhan & Stander, 1994;Van der Walt & Maree, 2007). The students" written responses to the problem, and the questionnaire, and semi-structured interview records revealed that using metacognitive skills was associated with problem-solving and positively affected problem-solving results.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognition is what one knows about his/her own thinking ways and how he /she monitors and regulates his/her thinking processes while engaging in a task (Goos, Galbraith & Renshaw, 2000). The concept of metacognition is defined by many researchers (Biryukov, 2003;Goh, 2008;Hecker, 1998;Iwai, 2011;Koriat, 2007;Salam, Misu, Rahim, Hindaryatiningsih & Ghani, 2020;Wells, 2009). For instance, to Koriat (2007) metacognition means what people know about cognition, their cognitive processes and how they use metacognition knowledge to adjust their information processes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For the conceptual and procedural and multidimensional literacy group, the characteristics of metacognition that arise during problem solving are the use of various strategies to demonstrate or improve the accuracy of their thinking (making sketches, drawing), analyzing problems before solving them, understanding and mastering the mathematical concepts underlying the given problem, even though In some steps, it was difficult to check, but due to a lack of conceptual knowledge, the answers given were not correct (Amin & Mariani, 2017;Bakar & Ismail, 2020;Kramarski & Zoldan, 2008;Salam et al, 2020;Schneider & Artelt, 2010;Su et al, 2016;Zepeda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%